Social Marketing : Behavior Change for Good - Lee, Nancy R. (SAGE Publications, Inc. (US), 2023)
Successful social marketing holds the power to change the world.  Social Marketing: Behavior Change for Good, 7th Edition is the definitive guide for designing and implementing memorable social marketing campaigns. Authors Nancy R. Lee, Philip Kotler, and Julie Colehour present a proven 10-step strategic marketing plan and guides students through each stage of the process. The 7th Edition is packed with 12 new cases and dozens of new examples related to today′s most pressing social problems including the COVID-19 pandemic, natural disasters, equity and inclusion, and homelessness. The new edition also includes significantly expanded coverage of social media. Whether your students are on a mission to improve public health,  protect the environment, or galvanize their community, they will find Social Marketing an invaluable resource.